Preoperative therapy for pancreatic adenocarcinoma—precision beyond anatomy. Issue 16 (9th June 2022) - Seo, Y. David; Katz, Matthew H. G.
Abstract: Despite recent advances in the systemic treatment of gastrointestinal tumors, pancreatic adenocarcinoma (PDAC) remains a challenging disease, with 5‐year survival just over 10%. Pancreatectomy in patients meeting defined anatomic criteria can result in cure; however, perioperative morbidity and mortality, as well as high rates of both local and distant recurrence even after "potentially curative" resection, have limited survival. Although perioperative chemotherapy has been shown to improve patients' longevity and chance for cure, debate continues about whether the preoperative or adjuvant approach is most effective in treatment of localized PDAC. Large, randomized multicenter trials in patients with resectable and borderline resectable PDAC have evaluated an evolving therapeutic landscape with mixed results. Importantly, these landmark studies share the fundamentally flawed assumption that tumor anatomical characteristics are an indicator of behavior and natural history. Concurrent biologic and translational research has revealed that rather than a single disease, PDAC represents a phenotypically variable group of malignancies arising in physiologically diverse patients. Ongoing novel trials have begun to capture this heterogeneity both in patient selection as well as the measurement of response by using genomic, transcriptional and radiomic markers. By moving away from classic anatomic descriptors to a more nuanced landscape of biomarkers predictive of tumor behavior and response, we can further refine the questions asked in preoperative trials and translate the answers to clinically meaningful precision therapy in localized PDAC. Abstract : The concurrent evolution of perioperative therapy, surgery and multidisciplinary care have resulted in hard‐fought gains in survival for patients with pancreatic cancer. In the management of localized PDAC, the focus on classic anatomic descriptors of tumor resectability must yield to a more nuanced focus on biomarkers of cancer behavior and response.